Catalytic partial oxidation of CH4 over bimetallic Ni‐Re/Al2O3: Kinetic determination for application in microreactor. Issue 5 (5th December 2017) - Bawornruttanaboonya, Kuson; Laosiripojana, Navadol; Mujumdar, Arun S.; Devahastin, Sakamon
Abstract : The activity of a novel Ni‐Re/Al2 O3 catalyst toward partial oxidation of methane was investigated in comparison with that of a precious‐metal Rh/Al2 O3 catalyst. Reactions involving CH4 /O2 /Ar, CH4 /H2 O/Ar, CH4 /CO2 /Ar, CO/O2 /Ar, and H2 /O2 /Ar were performed to determine the kinetic expressions based on indirect partial oxidation scheme. A mathematical model comprising of Ergun equation as well as mass and energy balances with lumped indirect partial oxidation network was applied to obtain the kinetic parameters and then used to predict the reactant and product concentrations as well as temperature profiles within a fixed‐bed microreactor. H2 and CO production as well as H2 /CO2 and CO/CO2 ratios from the reaction over Ni‐Re/Al2 O3 catalyst were higher than those over Rh/Al2 O3 catalyst. Simulation revealed that much smoother temperature profiles along the microreactor length were obtained when using Ni‐Re/Al2 O3 catalyst. Steep hot‐spot temperature gradients, particularly at the entrance of the reactor, were, conversely, noted when using Rh/Al2 O3 catalyst. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1691–1701, 2018